Design High Efficiency Buck-Boost Converter Using MOSFET - Pooja Ramdas Makhare; Pooja Ramdas Makhare; Prathamesh Vijay Ambi; Sandip Pravin Dhumal; Prof. Udamale S.R (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The rapid expansion of electric vehicles, renewable energy sources, and DC microgrids has heightened the demand for versatile power converters capable of bidirectional operation and high efficiency. This paper presents the design, implementation, and experimental validation of a MOSFET-based bidirectional buck–boost DC–DC converter, controlled by a PIC16F877A microcontroller. Leveraging low-RDS(on) power MOSFETs and opto-isolated gate drivers, the proposed system seamlessly transitions between buck and boost modes to manage energy flow between a low-voltage battery bank and variable DC sources. Detailed characterization in both simulation and hardware prototypes demonstrates peak efficiencies exceeding 95 %, low ripple, and rapid transient response — critical metrics for applications such as regenerative braking in electric vehicles, battery charge/discharge management, and renewable integration. To facilitate reproducibility and future enhancements, we outline the converter’s topology, control algorithm, hardware and software requirements, and system architecture. A comprehensive literature review anchors our contributions within the field, comparing performance metrics against existing MOSFET- and IGBT-based bidirectional converters.